The Effect of Financial Distress and Transfer Pricing on Tax Avoidance in Multinational Companies Listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 Period - Sadjiarto, Arja; Prasetyo, Devina Jesslyn; Go, Valerie Angelica (Journal of International Conference Proceedings, 2023)
Due to the Covid-19 pandemic conditions from 2020 to 2022, many companies, including multinational corporations, experiencing financial difficulties tend to be more aggressive in tax avoidance to sustain the future viability of the company. On the other hand, companies also utilize transfer pricing mechanisms to avoid high tax payments. This research aims to examine the influence of financial distress and transfer pricing on tax avoidance in multinational companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. Multiple regression analysis is used to analyze the data collected from a sample of 122 multinational companies listed on the IDX. The research results indicate that financial distress has a positive influence, while transfer pricing has a negative influence on tax avoidance in multinational companies listed on the IDX. Therefore, multinational companies in Indonesia need to consider these factors in managing their tax and financial risks. The implications of these research findings suggest that multinational companies in Indonesia need to consider these factors in managing their tax and financial risks.